AfroPerú: Tras las huellas de la negritud en el Perú (Altre Modernità, 2011)
The purpose of this article is to develop a concrete investigation about the afro-descendants identities innowadays Peru through the analysis of the African presence in the colonial age, focusing on different phases suchas the abolition of slavery, the political independence and the statement of rights which for long time has beendenied to this social class, until the actuality. Further to the outlining of the historical and social background of theafro element’s complexity in the survey of the variegated biological and cultural Peruvian mosaic, this case studyfocus on the today’s afro-Peruvian identity’s question, investigating about characteristics, problems and ways ofinteraction with the rest of the Peruvian population. Moreover, this analysis keeps track of the “negritude”, thatis the afro movement, in the Peruvian art, literature and culture. Thanks to a study experience in Peru of theauthor, this piece offers also a picture of the current situation of afro-Peruvian communities and emphasizes thesocial and cultural initiatives and also political measures taken in the last years in order to assert the distinctivefeature of the afro-Peruvian identity in Peru and all over the world.